2020
DOI: 10.1002/fsn3.2074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plantago ovata Forsk seed mucilage on survivability of Lactobacillus acidophilus, physicochemical and sensory attributes of produced low‐fat set yoghurt

Abstract: Nowadays, consumers’ attention to the functional foods has increased significantly. In this study, the effect of different concentration (0.5, 1, and 2%) of P.ovata Forsk seed mucilage (PFM) on survivability of L.acidophilus, physicochemical, and sensory attributes of produced low‐fat yoghurt were investigated in 0, 7, 14, and 21 days of storage period. Results showed that at the beginning of the storage period, the number of L.acidophilus in yoghurt samples containing PFM was significantly higher than control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
4
8
1
Order By: Relevance
“…The increase in the fermentation rate seen in this study might be due to the high level of protein availability. The same phenomenon was observed in the yogurt enriched with protein ( Giacometti Cavalheiro et al, 2020 ; Mehrinejad Choobari et al, 2021 ). It has been reported that the presence of amino acids supported the growth of LAB and thus increased the fermentation rate ( Giacometti Cavalheiro et al, 2020 ; Mehrinejad Choobari et al, 2021 ).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The increase in the fermentation rate seen in this study might be due to the high level of protein availability. The same phenomenon was observed in the yogurt enriched with protein ( Giacometti Cavalheiro et al, 2020 ; Mehrinejad Choobari et al, 2021 ). It has been reported that the presence of amino acids supported the growth of LAB and thus increased the fermentation rate ( Giacometti Cavalheiro et al, 2020 ; Mehrinejad Choobari et al, 2021 ).…”
Section: Resultssupporting
confidence: 75%
“…The same phenomenon was observed in the yogurt enriched with protein ( Giacometti Cavalheiro et al, 2020 ; Mehrinejad Choobari et al, 2021 ). It has been reported that the presence of amino acids supported the growth of LAB and thus increased the fermentation rate ( Giacometti Cavalheiro et al, 2020 ; Mehrinejad Choobari et al, 2021 ). This phenomenon shows the importance of amino acids and protein from BSG extracts in reducing the fermentation period.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…[144]. Recently, P. ovata seed mucilage was demonstrated to act not only as a fat replacer in yogurt but also as a prebiotic [145]. Plantago mucilage has been proposed as a biosorbent in low-cost technology to remove heavy metal from water.…”
Section: Plantagomentioning
confidence: 99%
“…This result is aligned with current study in control with the lactic acid at a range of 0.33–0.38%. However, BSG derivatives enriched the lactic acid production up to 0.9% which is similar with milk-based yogurt ( Giacometti Cavalheiro et al, 2020 ; Gürbüz et al, 2021 ; Mehrinejad Choobari et al, 2021 ). By this, BSG derivatives might have improved the stability, growth and the survival rate of the LAB.…”
Section: Resultsmentioning
confidence: 69%